Rina a novel - Kang, Yŏng-suk 1966-; Boram, Kim (Victoria, TX Dalkey Archive Press, 2015)
Rina is a defector from a country that might be North Korea, traversing an "empty and futile" landscape. Along the way, she is forced to work at a chemical plant, murders a few people, becomes a prostitute, runs a lucrative bar, and finds a solace in a motley family of wanderers all as disenfranchised as she. Brutal and unflinching, with elements of the mythic and grotesque interspersed with hard-edged realism, Rina is a pioneering work of Korean postmodernism
Keywords: Muchachas adolescentes- Novela- -- Posmodernismo coreano